2022
DOI: 10.1101/2022.02.16.22271053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in air and on surfaces in rooms of infected nursing home residents

Abstract: There is an ongoing debate on airborne transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) as a risk factor for infection. In this study, the level of SARS-CoV-2 in air and on surfaces of SARS-CoV-2 infected nursing home residents was assessed to gain insight in potential transmission routes. During outbreaks, air samples were collected using three different active and one passive air sampling technique in rooms of infected patients. Oropharyngeal swabs (OPS) of the residents and dry s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…This is in contrast with findings from previous outbreak investigations conducted at mink farms and nursing homes, where similar sampling technologies were applied [1,22]. In these studies, several air samples collected in COVID-19 infected mink farms, and a high percentage of both air and surface swab samples collected in rooms in nursing homes with SARS-CoV-2 positive patients [1,22]. A previous study in London also found limited evidence of SARS-CoV-2 contamination in school environments [18].…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…This is in contrast with findings from previous outbreak investigations conducted at mink farms and nursing homes, where similar sampling technologies were applied [1,22]. In these studies, several air samples collected in COVID-19 infected mink farms, and a high percentage of both air and surface swab samples collected in rooms in nursing homes with SARS-CoV-2 positive patients [1,22]. A previous study in London also found limited evidence of SARS-CoV-2 contamination in school environments [18].…”
Section: Discussioncontrasting
confidence: 87%
“…Although we found evidence of SARS-CoV-2 transmission within secondary schools, the lack of detectable SARS-CoV-2 RNA in collected air and surface samples suggests that major environmental contamination is uncommon in schools under the prevailing conditions at the time of the study. This is in contrast with findings from previous outbreak investigations conducted at mink farms and nursing homes, where similar sampling technologies were applied [1,22]. In these studies, several air samples collected in COVID-19 infected mink farms, and a high percentage of both air and surface swab samples collected in rooms in nursing homes with SARS-CoV-2 positive patients [1,22].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although early studies at times proposed that SARS‐CoV‐2 was sparsely found in the patient environment, the ubiquity of the environmental presence of the virus in contiguity to the infected patient soon became more obvious 1 . There has been a plethora of investigations since that corroborate the common environmental presence at least of viral RNA 19–36 . These positive determinations have included caregiver garments and accessories.…”
Section: Introductionmentioning
confidence: 99%
“…Paper, coins, and banknote materials also allow virus survival 46–49 . It is conceivable that inactive virus RNA may remain on surfaces for many days, thus jeopardizing the understanding of infectivity 28,37,50 . Virus strain variants may not differ in survival on some surfaces 51 .…”
Section: Introductionmentioning
confidence: 99%